EXPRESSIVE SPEECH ACTS ON NETIZENS’ COMMENTS IN JOE BIDEN’S INSTAGRAM ACCOUNT - Mega Bunga Indriyana; Yuyun Nurulaen; Erlan Aditya Ardiansyah (CALL, 2021)
United States presidential election 2020 is the most awaited event for the citizens of the United States. People usually want to get to know how good the presidential candidates are by searching for information about the presidential candidates. Checking the presidential candidates’ social media is one way to find outtheirprofiles.Joe Biden as one of the presidential candidates uses the growing popularity of Instagram to gain public attention by posting some of his responses to current issues and promoting himself as the next President of the United States. It made Joe Biden’s Instagram account is filled with netizens’ comments. This research aims to identify the expressive speech acts that appear in Joe Biden's comments published on September 13, 2020, to January 20, 2021, and to describe the reasons for their use of these expressive speech acts. The instrument of this research is a document.  The data were collected by browsing the comments on Joe Biden’s Instagram post, then the data were selected, and identified the expressive speech acts used by netizens, then the research showed the findings of the research by presenting data and analysis. There are 26 data contained an expressive speech act, in which 10 data as expressive of thanking, 3data as expressive of congratulating, 5 data as expressive of wishing, 8 data as expressive of attitude. The expressive speech act of thanking is the most dominant type of expressive speech act found on the netizens’ comments of Joe Biden Instagram post. In conclusion, netizens’ comments contained the expressive speech act of thanking since netizens appreciated the good things that Joe Biden had planned when he ran for President of the United States. Joe Biden frequently posts his thoughts on various issues and promises a good solution in the future. Netizens expressed their gratitude for Joe Biden because they felt they had found a leader who cared about society.Keywords: expressive speech act; instagram; Joe Biden; pragmatics, speech act